Normal sleep homeostasis and lack of epilepsy phenotype in GABA(A) receptor α3 subunit-knockout mice - Winsky-Sommerer, Raphaëlle (2008)
Thalamo-cortical networks generate specific patterns of oscillations during distinct vigilance states and epilepsy, well characterized by electroencephalography (EEG). Oscillations depend on recurrent synaptic loops, which are controlled by GABAergic transmission. In particular, GABA(A) receptors containing the α3 subunit are expressed predominantly in cortical layer VI and thalamic reticular nucleus (nRT) and regulate the activity and firing pattern of neurons in relay nuclei. Therefore, ablation of these receptors by gene targeting might profoundly affect thalamo-cortical oscillations. Here, we investigated the role of α3-GABA(A) receptors in regulating vigilance states and seizure activity by analyzing chronic EEG recordings in α3 subunit knockout (α3-KO) mice. The presence of postsynaptic α3-GABA(A) receptors/gephyrin clusters in the nRT and GABA(A)-mediated synaptic currents in acute thalamic slices were also examined. EEG spectral analysis showed no difference between genotypes during non rapid-eye movement (NREM) sleep or at waking-NREM sleep transitions. EEG power in the spindle frequency range (10–15 Hz) was significantly lower at NREM-REM sleep transitions in mutant compared to wild-type mice. Enhancement of sleep pressure by 6 h sleep deprivation did not reveal any differences in the regulation of EEG activities between genotypes. Finally, the waking EEG showed a slightly larger power in the 11–13-Hz band in α3-KO mice. However, neither behavior nor the waking EEG showed alterations suggestive of absence seizures. Furthermore, α3-KO mice did not differ in seizure susceptibility in a model of temporal lobe epilepsy. Strikingly, despite the disruption of postsynaptic gephyrin clusters, whole-cell patch clamp recordings revealed intact inhibitory synaptic transmission in the nRT of α3-KO mice. These findings show that the lack of α3-GABA(A) receptors is extensively compensated for to preserve the integrity of thalamo-cortical function in physiological and pathophysiological situations.